2019
DOI: 10.1177/1098612x19880435
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infection and subclinical bacteriuria in cats: A clinical update

Abstract: Practical relevance: Urinary tract infection (UTI) is an important cause of feline lower urinary tract disease (FLUTD), particularly in female cats older than 10 years of age. In addition to cats with typical clinical signs of FLUTD or upper UTI, many cats have subclinical bacteriuria, but the clinical relevance of this is currently uncertain. UTIs are one of the most important indications for antimicrobial use in veterinary medicine and contribute to the development of antimicrobial resistance. Adherence to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
108
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(118 citation statements)
references
References 116 publications
(221 reference statements)
3
108
0
7
Order By: Relevance
“…The results of our prospective study indicate that hyperthyroid cats have a low prevalence (<5%) of subclinical bacteriuria, nearly identical to that found in a cohort of euthyroid cats of similar age and sex presented for routine examination. This finding is in marked contrast to previous retrospective studies that reported a relatively high prevalence of UTI in hyperthyroid cats (12%‐22%), findings that have led to the widespread belief that hyperthyroid cats are at risk for developing subclinical bacteriuria 3,8‐10 . Our findings agree with other recent studies of mixed populations of cats, which failed to identify an increased risk of subclinical bacteriuria in much smaller cohorts of cats with hyperthyroidism 26,27 …”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The results of our prospective study indicate that hyperthyroid cats have a low prevalence (<5%) of subclinical bacteriuria, nearly identical to that found in a cohort of euthyroid cats of similar age and sex presented for routine examination. This finding is in marked contrast to previous retrospective studies that reported a relatively high prevalence of UTI in hyperthyroid cats (12%‐22%), findings that have led to the widespread belief that hyperthyroid cats are at risk for developing subclinical bacteriuria 3,8‐10 . Our findings agree with other recent studies of mixed populations of cats, which failed to identify an increased risk of subclinical bacteriuria in much smaller cohorts of cats with hyperthyroidism 26,27 …”
Section: Discussionsupporting
confidence: 78%
“…Although hematuria was common, it was not a predictor for subclinical bacteriuria in our study. Because cystitis can lead to the presence RBC in urine sediment, hematuria might be expected in cats with subclinical bacteriuria 3,26 . However, cystocentesis itself can induce transient microscopic hematuria indistinguishable from pathological hematuria, 38,39 and the number of RBCs in the sediment cannot be used as a reliable predictor of a positive urine culture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Therefore, urine stasis can predispose to pyelonephritis. 14,[28][29][30][31][32] The incomplete pigtail formation was also observed by others in a very recent study; despite intraoperative fluoroscopy, penetration of the kidney with subcapsular leakage was noted postoperatively. In the same study, an incomplete deployed pigtail led to obstruction of the nephrostomy catheter in one cat, leading to euthanasia.…”
Section: Discussionsupporting
confidence: 75%